Streptococcus iniae infection in cultured Asian sea bass (Lates calcarifer) and red tilapia (Oreochromis sp.) in southern Thailand - Kidchakan Supamattaya; Chutima Tantikitti; Ronald L. Thune; Toshiaki Itami; Nirut Sukkasame; Nopparat Tanmark; Terutoyo Yoshida; Naraid Suanyuk (Songklanakarin Journal of Science and Technology (SJST), 2010)
Streptococcal infections are becoming an increasing problem in aquaculture and have been reported worldwide in avariety of fish species. Here we describe the isolation and characterization of Streptococcus iniae from Asian sea bass (Latescalcarifer) and red tilapia (Oreochromis sp.) cultured in southern Thailand. Conventional and rapid identification systems,as well as the polymerase chain reaction (PCR), were used to determine that the isolate was S. iniae. The virulence of thisS. iniae was higher in Asian sea bass than in red tilapia, as shown by the 10 day-LD50 in Asian sea bass and red tilapia, being1.08x104 and 1.14x107 CFU, respectively. Histopathological changes in Asian sea bass are more severe than those observedin red tilapia. The changes can be found in several organs including liver, pancreas, heart, eye and brain. Histopathologicalfindings included cellular necrosis, infiltration of lymphocytes and granuloma formation in the infected organs.